Analisis Budaya Pelaporan Insiden Keselamatan Pasien Pada Perawat di Rumah Sakit Umum Daerah (RSUD) Sawerigading Palopo - Patmawati, Try Ayu; R Djano, Nur Asphina (Jurnal Keperawatan Muhammadiyah, 2020)
Objective:  to analyze the culture of incident reporting of patient safety to nurses at the Sawerigading Palopo Hospital.Methods: This article used  descriptive analytic with a cross sectional design. The population in this study were nurses at Sawerigading Palopo Hospital with a sample of this study as many as 63 nurses, sampling using purposive sampling technique. The instrument used was the IRCQ (Incident Reporting Culture Questionnaire).Results:  This study was found that from 63 respondents there were 38 respondents (60.3%) who showed a negative response to incident reporting culture and positive response about 25 people (39.7%). Based on the subscale, the factor that received the greatest negative response was the factor "Collegial atmospheres of unpleasantness and punishment" with a total of 47 respondents (74.6%).  Conclusion: The culture of incident reporting at the Sawerigading Palopo hospital have to be improved by maintaining the three factors that have received a positive response, while for the  Collegial atmospheres of unpleasantness and punishment still needs to be improved by minimizing any worries from nurses regarding punishment and fear. Therefore it is important for all boards of directors and management to monitor and evaluate the culture of incident reporting in order to improve patient safety Objective:  to analyze the culture of incident reporting of patient safety to nurses at the Sawerigading Palopo Hospital.Methods: This article used  descriptive analytic with a cross sectional design. The population in this study were nurses at Sawerigading Palopo Hospital with a sample of this study as many as 63 nurses, sampling using purposive sampling technique. The instrument used was the IRCQ (Incident Reporting Culture Questionnaire).Results:  This study was found that from 63 respondents there were 38 respondents (60.3%) who showed a negative response to incident reporting culture and positive response about 25 people (39.7%). Based on the subscale, the factor that received the greatest negative response was the factor "Collegial atmospheres of unpleasantness and punishment" with a total of 47 respondents (74.6%).Conclusion: The culture of incident reporting at the Sawerigading Palopo hospital have to be improved by maintaining the three factors that have received a positive response, while for the  Collegial atmospheres of unpleasantness and punishment still needs to be improved by minimizing any worries from nurses regarding punishment and fear. Therefore it is important for all boards of directors and management to monitor and evaluate the culture of incident reporting in order to improve patient safety